If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(3y + 8x) = 0 Reorder the terms: 7x + -1(8x + 3y) = 0 7x + (8x * -1 + 3y * -1) = 0 7x + (-8x + -3y) = 0 Combine like terms: 7x + -8x = -1x -1x + -3y = 0 Solving -1x + -3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. -1x + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 -1x + 0 = 0 + 3y -1x = 0 + 3y Remove the zero: -1x = 3y Divide each side by '-1'. x = -3y Simplifying x = -3y
| 0=-2(4+3v)-8(-8v-1) | | 7U-14=3U+14 | | x+4=-4+9 | | x[x-4]=96 | | 29=a+76 | | 4(0.5x+0.25)+2=2(4x+24) | | 2(5t-3)-t=3(3t-2) | | 9(b+7)+4b=-6b-6(b+2) | | 2x^3-x^2-3x=0 | | x+5=-x+9 | | 12x=11x-1188 | | 6=-6+b | | 0.66666666666(x-3)+6=0.16666666666666666666(4x+24) | | -2X-24=27 | | x=(1-0.510)/(1) | | x+5=-5x-5 | | x+5=-5x-5 | | x+5=-5x-5 | | x+5=-5x-5 | | 30-6x=0 | | 56=-4(-6+4n)-8(n+2) | | 2z-(1-z)=11-z | | 0.66(6x-5)=2-0.33(3x-2) | | 25=3n-7 | | 30=4t-19t | | 4=3x-2 | | 2(2x+3)=4x+3 | | 6x+1=4x-7 | | 12x=11x-1080 | | -(x+5)-8(1-2x)=32 | | X=-2+9 | | 5w-7w=-16 |